Zn-bamboo charcoal fiber cloth composite electrode material and preparation method and application thereof
By electrodepositing zinc on bamboo charcoal fiber cloth, Zn/bamboo charcoal fiber cloth composite electrode material was prepared, which solved the stability and capacity attenuation of the existing zinc ion battery negative electrode materials, and achieved high energy density, stability and low cost electrode materials.
Patent Information
- Application Number
- CN202411797616.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-09
- Publication Date
- 2025-03-04
AI Technical Summary
The existing zinc ion battery negative electrode materials are prone to dendrite growth, poor structural stability, and fast capacity attenuation during use, which limits its practical application in the field of energy storage.
The preparation method of Zn-bamboo charcoal fiber cloth composite electrode material is adopted, and bamboo fiber is carbonized into bamboo charcoal fiber cloth by high temperature treatment, and zinc is loaded thereon by electrodeposition method to form the Zn/bamboo charcoal fiber cloth composite electrode material.
The prepared Zn/bamboo charcoal fiber cloth composite electrode material has high energy density and power density, good stability, low cost, and is not easy to deform in the air and is easy to store.
Smart Images

Figure CN119560542A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite electrode materials, and in particular to a Zn-bamboo charcoal fiber cloth composite electrode material and a preparation method and application thereof. Background Art
[0002] With the continuous growth of energy demand and the increasingly severe environmental problems, the development of efficient and green energy storage technology has become a hot area of global scientific research. Zinc-ion Batteries (ZIBs), as a new energy storage technology, have shown great application prospects in renewable energy storage, portable devices and large-scale energy storage systems due to their advantages such as high safety, low cost, environmental protection and abundant zinc resources.
[0003] One of the key components of zinc-ion batteries is the negative electrode material, whose performance directly affects the energy density, cycle life and rate performance of the battery. Ideal zinc-ion negative electrode materials need to have the following characteristics: high conductivity to reduce the internal resistance loss of the electrode, excellent electrochemical activity to support efficient charge storage and transfer, stable structure to ensure cycle life, and good mechanical strength to ensure durability. At present, commonly used zinc-ion negative electrode materials mainly include metal zinc foil and other zinc-based alloy materials. However, these materials often face a series of problems in actual use, such as: safety hazards caused by easy dendrite growth, poor structural stability, rapid capacity decay, etc., which seriously limit their practical application in the field of energy storage. Summary of the invention
[0004] One of the purposes of the present invention is to provide a method for preparing a Zn-bamboo charcoal fiber cloth composite electrode material. The prepared electrode material has high energy density and power density, good stability, and low cost.
[0005] In order to achieve the above object, the present invention adopts the following technical scheme: a method for preparing a Zn-bamboo charcoal fiber cloth composite electrode material, comprising the following steps: S1. Carbonizing bamboo fiber into bamboo charcoal fiber under high temperature treatment to obtain bamboo charcoal fiber cloth; S2. Prepare a zinc salt solution, use the zinc salt solution as an electrolyte, and use the zinc electrodeposition method to perform zinc electrodeposition on the bamboo charcoal fiber cloth to obtain a Zn-bamboo charcoal fiber cloth composite electrode material.
[0006] Furthermore, in step S1, the temperature of the high temperature treatment is 400-1500° C., and the time is 60-180 min.
[0007] Furthermore, in step S1, the bamboo fiber is selected from at least one (for example, one of) bamboo raw fiber and bamboo pulp fiber.
[0008] Furthermore, in step S1, after the bamboo fiber is carbonized into bamboo charcoal fiber, the surface of the bamboo fiber is modified to improve its hydrophilicity.
[0009] Among them, the surface modification methods include but are not limited to coating modification, high temperature modification, and composite surface modification.
[0010] Specifically, the modification steps can be: immersing the bamboo charcoal fiber in a solution containing 10% polyamic acid solution and N'N-dimethylformamide as solvent for six hours, and then placing the bamboo charcoal fiber cloth in a nitrogen atmosphere at 600°C for high temperature treatment, and heating at a constant temperature for 120 minutes, wherein the heating rate is 10°C·min -1 , the surface of bamboo charcoal fiber cloth is modified.
[0011] Alternatively, the modification step may be: immersing the bamboo charcoal fiber cloth in a 3% nitric acid solution at a constant temperature of 80° C. for six hours to chemically modify the surface of the bamboo charcoal fiber cloth.
[0012] Alternatively, the modification step may be: placing the bamboo charcoal fibers in a muffle furnace, and heat treating the bamboo charcoal fiber cloth in an air atmosphere at 300° C. for 2 hours to perform hot air treatment modification on the bamboo charcoal fiber cloth.
[0013] Alternatively, the modification step may be: immersing the bamboo charcoal fiber cloth in a 3% potassium permanganate solution at a constant temperature of 80° C. for six hours to chemically modify the surface of the bamboo charcoal fiber cloth.
[0014] Furthermore, in step S2, the zinc salt solution is selected from at least one (for example, one of) zinc sulfate solution, zinc chloride solution, zinc nitrate solution, and zinc acetate solution.
[0015] Furthermore, in step S2, the concentration of the zinc salt solution is 0.001 to 1 mol·L -1 .
[0016] Furthermore, in step S2, a three-electrode system is used to electro-deposit the bamboo charcoal fiber cloth, wherein the bamboo charcoal fiber cloth is used as a working electrode, a carbon rod is used as a counter electrode, and a calomel electrode is used as a reference electrode, and Zn is loaded on the bamboo charcoal fiber cloth in a zinc salt solution.
[0017] Furthermore, in step S2, during the electrodeposition process, the method adopted is constant current deposition method, constant potential deposition method or cyclic voltammetry deposition method.
[0018] Furthermore, in step S2, during the electrodeposition process, the voltage is 0.1-1.5V, the deposition time is 10s-3000s, and the electrolyte temperature is 20-50°C.
[0019] Another object of the present invention is to provide a Zn-bamboo charcoal fiber cloth composite electrode material, which is prepared by the above-mentioned preparation method.
[0020] In addition, the present invention also provides a zinc ion battery, which uses the above-mentioned Zn-bamboo charcoal fiber cloth composite electrode material as a negative electrode material.
[0021] The Zn / bamboo charcoal fiber cloth composite electrode material prepared by the present invention is to load the Zn active substance on the bamboo charcoal fiber cloth. Compared with the traditional loading on carbon materials, conductive materials, and metal materials, the raw material price of the bamboo charcoal fiber cloth is relatively low and has relatively good electrochemical performance. Moreover, the preparation process of the present invention is simple, and electrodes of various sizes can be prepared. The prepared Zn / bamboo charcoal fiber cloth composite electrode material has stable performance, is not easy to be denatured in the air, and is easy to store. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a SEM image of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 2 This is a SEM image of a single bamboo fiber of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 3 This is the EDS element distribution diagram of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 4 This is a Zn element distribution diagram of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 5 Element content diagram of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 6 : is the charge and discharge curve of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1; Figure 7 1 is the cyclic voltammetry curve of the Zn / bamboo charcoal fiber cloth composite electrode material prepared in Example 1. DETAILED DESCRIPTION
[0023] In order to facilitate the understanding of those skilled in the art, the present invention is further described below in conjunction with the examples, and the contents mentioned in the examples are not limitations of the present invention. It should be noted in advance that the following examples were completed in the laboratory, and those skilled in the art should understand that the amounts of the components given in the examples only represent the ratio relationship between the components, rather than specific limitations.
[0024] As a renewable material with wide sources, low cost, excellent mechanical strength and conductivity, bamboo charcoal fiber cloth has received increasing attention in the field of energy storage in recent years. Its porous structure and surface functional groups give it good ion adsorption capacity and ion transport channels, making it a potential application advantage in electrode materials. However, the electrochemical activity of bamboo charcoal fiber cloth itself is low, and further modification is needed to improve its performance.
[0025] Among them, by introducing zinc (Zn) or its compounds into bamboo charcoal fiber cloth, its electrochemical activity, conductivity and ion storage capacity can be significantly improved, thereby overcoming the defects of traditional zinc ion negative electrode materials. In the preparation of composite materials, the porous structure of bamboo charcoal fiber cloth can not only provide good distribution and stability of zinc, but also effectively alleviate the growth of zinc dendrites, improving the safety and cycle performance of batteries.
[0026] Based on the above concept, the present invention develops a method for preparing an efficient and environmentally friendly Zn / bamboo charcoal fiber cloth composite zinc ion negative electrode material, which can not only significantly improve the electrochemical performance of zinc ion batteries, but also provide a new technical direction for sustainable energy storage technology, which has important scientific significance and practical value for promoting the widespread application of zinc ion batteries.
[0027] The preparation method of the Zn / bamboo charcoal fiber cloth composite electrode material provided by the present invention mainly comprises the following steps: S1. Cut bamboo fiber into rectangles of specific size (such as 1×1.5 cm), wash with deionized water and dry, treat the bamboo fiber cloth at 400-1500° C. for 60-180 min in an inert gas atmosphere to obtain bamboo charcoal fiber cloth, and perform surface modification on the bamboo charcoal fiber cloth to make it more hydrophilic.
[0028] S2. Place the bamboo charcoal fibers obtained above in a 0.001-1 mol·L -1 In the zinc salt solution, the electrolyte temperature is maintained at 20-50°C. The electrodeposition adopts a three-electrode system, with bamboo charcoal fiber cloth as the working electrode, carbon rod as the counter electrode, and calomel electrode as the reference electrode, and Zn is loaded on the carbon cloth fiber in the zinc salt solution. The electrodeposition conditions are: constant current deposition, constant potential deposition or cyclic voltammetry deposition. The voltage is 0.1-1.5V, the deposition time is 10s-3000s, and the electrolyte temperature is 20-50°C.
[0029] The above preparation process is simple and controllable, and the prepared electrode material has high energy density and power density, good stability, and low cost.
[0030] The following is further explained with specific examples. Example 1
[0031] 1. Preparation of Zn / bamboo charcoal fiber cloth composite electrode material.
[0032] Step 1: Cut the bamboo fiber into 1×1.5 cm rectangles, wash with deionized water and dry, and place the bamboo fiber cloth in a nitrogen atmosphere at 400°C for high temperature treatment. Keep the temperature constant for 120 min, with a heating rate of 10°C min -1 , so that the bamboo fiber cloth is carbonized into bamboo charcoal fiber cloth; the bamboo charcoal fiber cloth is then immersed in a solution of 10% polyamic acid solution and N'N-dimethylformamide solvent for six hours, and then the bamboo charcoal fiber cloth is placed in a nitrogen atmosphere at 600℃ for high temperature treatment, and the temperature is kept constant for 120 min, with a heating rate of 10℃·min -1 , the surface of bamboo charcoal fiber cloth is modified.
[0033] Step 2: Prepare electrolyte: 0.43 mol·L -1 The electrolyte was placed in a 30°C water bath for ten minutes. The electrodeposition used a three-electrode system, with bamboo charcoal fiber cloth as the working electrode, carbon rod as the counter electrode, and calomel electrode as the reference electrode. The bamboo charcoal fiber was electrodeposited at a constant voltage of 0.874 V and a deposition time of 150 s to load Zn on the bamboo charcoal fiber. After the electrodeposition was completed, it was taken out, washed with deionized water, and dried to obtain a Zn / bamboo charcoal fiber cloth composite electrode material.
[0034] 2. Electrochemical performance test.
[0035] The prepared Zn / bamboo charcoal fiber cloth composite electrode material and α-MnO2 were used as the counter electrode to assemble a Zn||MnO2 battery for electrochemical performance testing. The electrolyte was 2 mol·L -1 ZnSO4 and 0.2 mol·L -1 MnSO4 mixed solution. At 0.2A·g -1 The discharge capacity after 200 cycles is 398.5 mAh g −1 , at 3 A·g -1 The capacity retention rate is 69% after 1500 cycles.
[0036] also, Figure 1 Shows the SEM image of the Zn / bamboo charcoal fiber cloth composite electrode material; Figure 2 The SEM image of a single bamboo fiber of the Zn / bamboo charcoal fiber cloth composite electrode material is shown; Figure 3 The EDS element distribution diagram of Zn / bamboo charcoal fiber cloth composite electrode material is shown; Figure 4 The Zn element distribution diagram of the Zn / bamboo charcoal fiber cloth composite electrode material is shown; Figure 5 The element content diagram of Zn / bamboo charcoal fiber cloth composite electrode material is shown; Figure 6 The charge and discharge curves of Zn / bamboo charcoal fiber cloth composite electrode material are shown; Figure 7 The cyclic voltammetry curve of Zn / bamboo charcoal fiber cloth composite electrode material is shown. Example 2
[0037] 1. Preparation of Zn / bamboo charcoal fiber cloth composite electrode material.
[0038] Step 1: Cut the bamboo fiber into 1×1.5 cm rectangles, wash with deionized water and dry, and place the bamboo fiber cloth in a nitrogen atmosphere at 900°C for high temperature treatment. Keep the temperature constant for 90 min, with a heating rate of 10°C·min -1 , so that the bamboo fiber cloth is carbonized into bamboo charcoal fiber cloth; then the bamboo charcoal fiber cloth is immersed in a 3% nitric acid solution at a constant temperature of 80°C for six hours to carry out surface chemical modification of the bamboo charcoal fiber cloth.
[0039] Step 2: Prepare electrolyte: 0.001 mol·L -1 The zinc chloride solution was placed in a 20°C water bath for ten minutes. The electrodeposition used a three-electrode system, with bamboo charcoal fiber cloth as the working electrode, carbon rod as the counter electrode, and calomel electrode as the reference electrode. Zn was loaded on the bamboo charcoal cloth fibers at a constant voltage of 0.1 V and a deposition time of 3000 s in the electrolyte. After the electrodeposition was completed, it was taken out, washed with deionized water, and dried. The Zn / bamboo charcoal fiber cloth composite electrode material was obtained.
[0040] 2. Electrochemical performance test.
[0041] The prepared Zn / bamboo charcoal fiber cloth composite electrode material and α-MnO2 were used as the counter electrode to assemble a Zn||MnO2 battery for electrochemical performance testing. The electrolyte was 2 mol·L -1 ZnSO4 and 0.2 mol·L -1 MnSO4 mixed solution. At 0.2A·g -1 The discharge capacity after 200 cycles is 395.5 mAh g −1 , at 3 A·g -1 The capacity retention rate is 68% after 1500 cycles. Example 3
[0042] 1. Preparation of Zn / bamboo charcoal fiber cloth composite electrode material.
[0043] Step 1: Cut the bamboo fiber into 1×1.5 cm rectangles, wash with deionized water and dry, and place the bamboo fiber cloth in a nitrogen atmosphere at 1200°C for high temperature treatment. Keep the temperature constant for 60 min, with a heating rate of 10°C min -1, so that the bamboo fiber cloth is carbonized into bamboo charcoal fiber cloth; then the bamboo charcoal fiber is arranged in a muffle furnace, and heat-treated at 300°C for 2 hours in an air atmosphere to modify the bamboo charcoal fiber cloth through hot air treatment.
[0044] Step 2: Prepare electrolyte: 0.5 mol·L -1 The zinc nitrate solution was placed in a 40°C water bath for ten minutes. The electrodeposition used a three-electrode system, with bamboo charcoal fiber cloth as the working electrode, carbon rod as the counter electrode, and calomel electrode as the reference electrode. Zn was loaded on the bamboo charcoal cloth fibers at a constant voltage of 0.9V and a deposition time of 1000s in the electrolyte. After the electrodeposition was completed, it was taken out, washed with deionized water, and dried. The Zn / bamboo charcoal fiber cloth composite electrode material was obtained.
[0045] 2. Electrochemical performance test.
[0046] The prepared Zn / bamboo charcoal fiber cloth composite electrode material and α-MnO2 were used as the counter electrode to assemble a Zn||MnO2 battery for electrochemical performance testing. The electrolyte was 2 mol·L -1 ZnSO4 and 0.2 mol·L -1 MnSO4 mixed solution. At 0.2A·g -1 The discharge capacity after 200 cycles is 392.5 mAh g −1 , at 3 A·g -1 The capacity retention rate is 62% after 1500 cycles. Example 4
[0047] 1. Preparation of Zn / bamboo charcoal fiber cloth composite electrode material.
[0048] Step 1: Cut the bamboo pulp fiber into 1×1.5 cm rectangles, wash with deionized water and dry, and place the bamboo pulp fiber cloth in a nitrogen atmosphere at 1500℃ for high temperature treatment for 180 minutes, with a heating rate of 10℃·min -1 , so that the bamboo pulp fiber cloth is carbonized into bamboo charcoal fiber cloth; then the bamboo charcoal fiber cloth is immersed in a 3% potassium permanganate solution at a constant temperature of 80°C for six hours to carry out surface chemical modification of the bamboo charcoal fiber cloth.
[0049] Step 2: Prepare electrolyte: 1.0 mol / L zinc acetate solution, and keep the electrolyte in a 50℃ water bath for ten minutes. Electrodeposition uses a three-electrode system, with bamboo charcoal fiber cloth as the working electrode, carbon rod as the counter electrode, and calomel electrode as the reference electrode. Zn is loaded on the bamboo charcoal cloth fiber at a constant voltage of 1.5 V and a deposition time of 10 s in the electrolyte. After the electrodeposition is completed, take it out, wash it with deionized water, and dry it. Get the Zn / bamboo charcoal fiber cloth composite electrode material.
[0050] 2. Electrochemical performance test.
[0051] The prepared Zn / bamboo charcoal fiber cloth composite electrode material and α-MnO2 were used as the counter electrode to assemble a Zn||MnO2 battery for electrochemical performance testing. The electrolyte was 2 mol·L -1 A mixed solution of 0.2 mol / L ZnSO4 and 0.2 mol / L MnSO4. -1 The discharge capacity after 200 cycles is 390.5 mAh g −1 , at 3 A·g -1 The capacity retention rate is 65% after 1500 cycles.
[0052] In summary, the present invention provides a method for preparing a Zn / bamboo charcoal fiber cloth self-supporting composite electrode material, firstly, bamboo fiber cloth is treated at high temperature to obtain bamboo charcoal fiber cloth, surface modification is performed to obtain modified bamboo charcoal fiber cloth, and then the obtained bamboo charcoal fiber cloth is electro-deposited on the bamboo charcoal fiber cloth by using a zinc salt solution as an electrolyte using an electro-deposition method of zinc to obtain a Zn / bamboo charcoal fiber cloth electrode material. The preparation process is simple and controllable, and the obtained Zn / bamboo charcoal fiber cloth self-supporting composite electrode material has good electrochemical performance and is safe, and the raw materials used are easily available and low in cost.
[0053] The above embodiments are preferred implementation schemes of the present invention. In addition, the present invention may also be implemented in other ways. Any obvious replacement without departing from the concept of the present technical solution is within the protection scope of the present invention.
[0054] Finally, it should be emphasized that in order to allow ordinary technicians in the field to more easily understand the improvements of the present invention over the prior art, some descriptions of the present invention have been simplified, and for the sake of clarity, some other elements are omitted in this application document. Those skilled in the art should realize that these omitted elements may also constitute the content of the present invention.
Claims
1. A method for preparing a Zn-bamboo charcoal fiber cloth composite electrode material, characterized in that: The steps include: S1. Carbonizing bamboo fiber into bamboo charcoal fiber under high temperature treatment to obtain bamboo charcoal fiber cloth; S2. Using zinc salt solution as electrolyte, bamboo charcoal fiber cloth is electroplated to obtain Zn-bamboo charcoal fiber cloth composite electrode material.
2. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 1, characterized in that: In step S1, the high temperature treatment is performed at a temperature of 400 to 1500° C. for a time of 60 to 180 minutes.
3. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 1, characterized in that: In step S1, the bamboo fiber is selected from at least one of bamboo raw fiber and bamboo pulp fiber.
4. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 1, characterized in that: In step S2, the zinc salt solution is selected from at least one of zinc sulfate solution, zinc chloride solution, zinc nitrate solution and zinc acetate solution.
5. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 1, characterized in that: In step S2, the concentration of the zinc salt solution is 0.001 to 1 mol·L -1 .
6. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 1, characterized in that: In step S2, a three-electrode system is used to electro-deposit the bamboo charcoal fiber cloth, wherein the bamboo charcoal fiber cloth is used as a working electrode, a carbon rod is used as a counter electrode, and a calomel electrode is used as a reference electrode, and Zn is loaded on the bamboo charcoal fiber cloth in a zinc salt solution.
7. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 6, characterized in that: In step S2, during the electrodeposition process, the method used is constant current deposition method, constant potential deposition method or cyclic voltammetry deposition method.
8. The method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to claim 6, characterized in that: In step S2, during the electrodeposition process, the voltage is 0.1-1.5V, the deposition time is 10s-3000s, and the electrolyte temperature is 20-50°C.
9. A Zn-bamboo charcoal fiber cloth composite electrode material, characterized in that: The composite electrode material is prepared by the method for preparing the Zn-bamboo charcoal fiber cloth composite electrode material according to any one of claims 1 to 8.
10. A zinc ion battery, characterized in that: The Zn-bamboo charcoal fiber cloth composite electrode material according to claim 9 is used as the negative electrode material of the battery.
Citation Information
Cited By
Bamboo charcoal integrated electrode and preparation method and application thereof
CN121215776A